(untitled) (Research, Society and Development, 2021)
Vitamin D (DV) is a pre-hormone and performs several functions: regulator of bone development, has antiviral, antifibrotic, immunomodulatory activities, and according to studies it may be able to reduce the risk of death from coronavirus infection, virus that was first identified in Wuhan (China) in December 2019 and spread rapidly around the world. Thus, the objective of this integrative review is to know what the world literature has published about the clinical importance of RV in preventing coronavirus infection. To search for the articles, the descriptors contained in the DeCs were used: [vitamin D / Vitamin D], [immunity / immunity] and [coronavirus infection / coronavirus infections], consulted in the Medline database. The inclusion criteria were: complete articles, available in Portuguese and English, published between 2011 and 04/2021. Thirty articles were selected in the English language, in which about 36.4% (11) discuss the factors that influence the serum levels of the RV organism and its implications for coronavirus infection, and 63.3% (19) address the mechanisms of action of the RV in the immune system in relation to coronavirus infection. It is known that the VD modulates the function of immune cells, in an innate-adaptive immune system interaction, regulates the expression and secretion of cytokines, therefore, the therapeutic intervention with VD can prevent and treat this disease, preventing mild cases from becoming serious. Therefore, supplementation would be the effective therapeutic tool to counter RV deficiency, but further clinical studies are needed to effectively prove its effectiveness.